2019
DOI: 10.1002/jcp.28355
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of OIP5‐AS1/HUR1 to discover new potential biomarkers and therapeutic targets in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a devastating autoimmune disease of the central nervous system associated with demyelination and axonal injury. This study was designed to find potential lncRNAs and their targets that are associated with the molecular basis of MS pathogenesis. In this study, peripheral blood samples were obtained from 50 relapsing‐remitting MS (RR‐MS) patients and 50 healthy controls. lncRNAs and their target were selected for validation using TaqMan Real‐Time PCR. Interactions were studied based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…LncRNAs have been proven to play important roles in IBD pathogenesis, including regulation of the intestinal epithelial barrier, cell apoptosis, and various immune system processes (138,139). There is growing evidence that lncRNAs may be promising diagnostic markers of various cancers, cardiovascular disease, and autoimmune disorders because they are relatively stable and simple to detect (140)(141)(142). Chen et al evaluated circulating lncRNAs levels of CD patients using microarray screening and qRT-PCR.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…LncRNAs have been proven to play important roles in IBD pathogenesis, including regulation of the intestinal epithelial barrier, cell apoptosis, and various immune system processes (138,139). There is growing evidence that lncRNAs may be promising diagnostic markers of various cancers, cardiovascular disease, and autoimmune disorders because they are relatively stable and simple to detect (140)(141)(142). Chen et al evaluated circulating lncRNAs levels of CD patients using microarray screening and qRT-PCR.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…Upregulation of AFAP1-AS1 promotes metastasis via modulation actin filament integrity ( 124 ). Due to its antiapoptotic properties in peripheral immune cells, it might be involved in the pathogenesis of MS ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…GAS8-AS1 has been downregulated, while AFAP-AS1 has been upregulated in MS patients. Regarding the role of AFAP1-AS1 in the pathogenesis and progression of MS, it can be hypothesized that dysregulation of GAS8-AS1 might be involved in the pathogenesis of MS (40,125). Zha et al revealed that GAS8-AS1 negatively regulated the expression of UCA1.…”
Section: Gas8-as1mentioning
confidence: 99%
“…Thus far, among these hub lncRNAs, DNAJC27-AS1, AF121898, and SNX29P2 have not been reported in any study. OIP5-AS1 is an antisense lncRNA that has been reported to play a critical role in various disorders, including oral squamous cell carcinoma [40], gastric cancer [41], cardiovascular disease [42], and multiple sclerosis [43]. Li and colleague's study revealed that OIP5-AS1 could promote the progression of oral squamous cell carcinoma by regulating the miR-338-3p/NRP1 axis [40].…”
Section: Discussionmentioning
confidence: 99%